Academic stress and depression among medical students - Rezki Perdani Sawai; Joki Perdani Sawai; Ummul Syamimi Lan Hawari; Abdul Rashid Abdul Aziz; Roslee Ahmad (Human Resource Management Academic Research Society (HRMARS), 2022)
Depression among university students is becoming a serious health issue in the country. Their vulnerability to higher rates of stressors has a negative impact on them as students as well as on their lives. This study investigates the level of academic stress and depression and the relationship between them among medical students at Universiti Sains Islam Malaysia (USIM). Questionnaires were given to 133 medical students at USIM comprising 3 sections covering demographic information, an academic stress inventory (SSI), and the Beck depression inventory (BDI). An analysis using Pearson’s correlation coefficient found a positive and significant relationship between the two variables. This study provides information to counselors on the level of academic stress and depression among students, especially medical students. It also aims to increase awareness among university authorities and parents on the importance of maintaining the mental health of students and children.